Sustainable manufacturing tactics and improvement methodology : a structured and systematic approach to identify improvement opportunities - Despeisse, Melanie (Cranfield University, 2013)
Growing environmental concerns caused by increasing consumption of natural resources and pollution need to be addressed. Manufacturing dictates the efficiency with which resource inputs are transformed into economically valuable outputs in the form of products and services. Consequently it is also responsible for the resulting waste and pollution generated from this transformation process. This research explored the challenges faced by sustainable manufacturing as a concept and as a model for manufacturing systems. The work is strongly based on the concepts of sustainability and industrial ecology applied at factory level. The research objectives were to understand what companies are doing to improve their sustainability performance at operational level (resource productivity) and to help other companies repeating such improvements in their own factory. In other words, the aim is to generalise sustainable practices across the manufacturing industry. The work started with a review of existing theories and practices for sustainable manufacturing and other related fields of research such as industrial ecology, cleaner production and pollution prevention. The concepts, themes, strategies and principles found in the literature provided a strong foundation to approach resource productivity improvements. The industrial cases collected gave an insight into the application of these strategies and principles in a factory. From the analysis of existing theories and practices, generic tactics were developed by translating 1000+ practices into generic rules and by mapping them against strategies and principles for sustainable manufacturing to check the completeness and consistency of the tactics library. To test the tactics and assist the user in their use through factory modelling, an improvement methodology was developed based on the same strategies and principles to provide a structured guide for accessing tactics and systematically identifying improvement opportunities. The research findings were tested with a series of prototype applications. These tests were carried out as part of a wider project (THERM). This project uses a modelling and simulation approach to capture the resource flows (material, energy, water and waste), the interactions within the manufacturing system (manufacturing operations, surrounding buildings and supporting facilities) and the influence of external factors‘ variation (weather conditions, building orientation and neighbouring infrastructures). The outcomes of the prototype applications helped develop and refine the research findings. The contribution to knowledge of this research resides in bridging the gap between high-level concepts for sustainability and industrial practices by developing a library of tactics to generalise sustainable manufacturing practices and an improvement methodology to guide the tactics implementation. From a practical viewpoint, the research provides a structured and systematic approach for manufacturers to undertake the journey towards more sustainable practice by improving resource flows in their factory.